64 Using Antithrombin Activity for Plasma Titration during Therapeutic Plasma Exchange in the Setting of Heparin Therapy: A Case Report. (11th January 2018) - Griggs, Joseph; Lockhart, Evelyn; Crookston, Kendall
Abstract: Transverse myelitis (TM) is a rare antibody-mediated segmental inflammation of the spinal cord which manifests with sensory, motor, and autonomic nervous system dysfunction. First-line treatment for TM is typically high-dose intravenous glucocorticoids; however, therapeutic plasma exchange (TPE) serves as an alternative treatment modality for those cases that fail to respond to glucocorticoids. Herein, we describe a case of a 63-year-old man who, while hospitalized for bilateral lower extremity paralysis due to TM, developed a deep vein thrombosis (DVT) for which he was treated with unfractionated heparin. The patient's TM symptoms showed no significant signs of improvement despite six daily treatments with 1 g methylprednisolone. A course of TPE was proposed; traditionally these procedures are performed with albumin as replacement fluid. However, albumin-based TPE procedures deplete plasma antithrombin (ATIII), which could place the patient at risk of heparin-resistance due to acquired ATIII deficiency. A combination of plasma and albumin was chosen as the replacement fluid, with plasma serving as a source of ATIII. Anti-factor Xa assays and ATIII levels were collected the morning of each scheduled TPE procedure; the anti-factor Xa assay ensured adequate heparin dosage, while the ATIII levels allowed for calculating plasma replacement volumes with a goal of maintaining ATIII levels greater than 50% following the procedure. At the conclusion of each TPE procedure, an additional ATIII level was checked to ensure the patient had ATIII levels greater than 50%. The patient finished all scheduled TPE procedures with ATIII levels maintained above 50% following each procedure. No exacerbation was observed of the patient's thromboembolism, and he regained partial mobility of his lower extremities by the end of his TPE course. In conclusion, when patients require TPE during heparin therapy for thromboembolism, we recommend monitoring ATIII levels to titrate plasma as TPE replacement fluid; this will help ensure adequate anticoagulation during the TPE course while minimizing unnecessary donor exposures to excessive plasma.